2020
DOI: 10.3390/ijms21155566
|View full text |Cite
|
Sign up to set email alerts
|

Passive Transfer of Sera from ALS Patients with Identified Mutations Evokes an Increased Synaptic Vesicle Number and Elevation of Calcium Levels in Motor Axon Terminals, Similar to Sera from Sporadic Patients

Abstract: Previously, we demonstrated increased calcium levels and synaptic vesicle densities in the motor axon terminals (MATs) of sporadic amyotrophic lateral sclerosis (ALS) patients. Such alterations could be conferred to mice with an intraperitoneal injection of sera from these patients or with purified immunoglobulin G. Later, we confirmed the presence of similar alterations in the superoxide dismutase 1 G93A transgenic mouse strain model of familial ALS. These consistent observations suggested that calcium plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…In our previous study, we demonstrated a significant calcium increase in the axon terminals of lumbar MNs in a similar experimental paradigm as in the present study [ 21 ]. To analyze whether analogous changes in the intracellular calcium could be evoked by the ALS serum treatment in the peripherally located motor axon terminals and the centrally located motoneuronal cell bodies, calcium data from these anatomical regions were pooled to patients serving as serum donors, plotted ( Figure 6 ), and evaluated using a linear regression analysis.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…In our previous study, we demonstrated a significant calcium increase in the axon terminals of lumbar MNs in a similar experimental paradigm as in the present study [ 21 ]. To analyze whether analogous changes in the intracellular calcium could be evoked by the ALS serum treatment in the peripherally located motor axon terminals and the centrally located motoneuronal cell bodies, calcium data from these anatomical regions were pooled to patients serving as serum donors, plotted ( Figure 6 ), and evaluated using a linear regression analysis.…”
Section: Resultssupporting
confidence: 81%
“…Meanwhile, healthy individuals, and patients with negative screening results for all 35 major ALS genes, regarded as sporadic ALS patients, served as the control. Using a short-term repeated injection paradigm, an increased synaptic vesicle density and increased calcium could be detected in the motor axon terminals of the injected mice [ 21 ], similar to those changes detected after the injection of sera from sporadic ALS patients [ 20 ] or seen in muscle biopsy samples of sporadic patients [ 17 ]. Furthermore, on the scatter diagram vesicle number and intracellular calcium, the population of ALS patients could be separated from the controls [ 21 ], again, similarly as in the case of human samples [ 17 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations